Increased risk of injury and adult attention deficit hyperactivity disorder and effects of pharmacotherapy: a nationwide longitudinal cohort study in South Korea - Ahn, Jaeun; Shin, Jae-won; Park, Haeyong; Ha, Joong-Won (Frontiers in Psychiatry, 2024)
Children and adolescents with attention deficit hyperactivity disorder (ADHD) are at an increased risk of accidents and injuries, and ADHD medication has been shown to mitigate this risk in these populations. However, the injury risk and the influence of ADHD medication in adults with ADHD remain unclear. This study aimed to investigate the injury risk in adults with ADHD and assess the impact of ADHD medication on this risk. Using a nationwide health claims database, we identified 9,417 adult patients with ADHD aged 19–44 years between 2017 and 2018. A retrospective propensity score-matched case-control study was conducted to examine the association between adult ADHD and injury risk across various categories. The effects of two commonly prescribed ADHD medications, methylphenidate and atomoxetine, were evaluated using a Cox proportional hazards model. The results showed that adults with ADHD had an increased risk of sustaining various types of injuries. Methylphenidate demonstrated a protective effect against injury, which persisted after adjusting for potential confounding factors. Similarly, atomoxetine significantly reduced the injury risk. These findings underscore the importance of injury prevention strategies in adults with ADHD and highlight the substantial health benefits of ADHD medications in this population.